2007
DOI: 10.1158/1535-7163.mct-06-0468
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fibroblast to myofibroblast transition by halofuginone contributes to the chemotherapy-mediated antitumoral effect

Abstract: Stromal myofibroblasts play an important role in tumor progression. The transition of fibroblasts to myofibroblasts is characterized by expression of smooth muscle genes and profuse synthesis of extracellular matrix proteins. We evaluated the efficacy of targeting fibroblast-to-myofibroblast transition with halofuginone on tumor progression in prostate cancer and Wilms' tumor xenografts. In both xenografts, low doses of halofuginone treatment, independent of the route of administration, resulted in a trend tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 44 publications
2
39
0
2
Order By: Relevance
“…The monoclonal antibody against FAP, sibrotuzumab, has been investigated in a Phase I clinical trial (11). In addition, an inhibitor of collagen I synthesis, halofuginone, prevents fibroblast differentiation to myofibroblasts and significantly reduces tumor progression when combined with low-dose chemotherapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…The monoclonal antibody against FAP, sibrotuzumab, has been investigated in a Phase I clinical trial (11). In addition, an inhibitor of collagen I synthesis, halofuginone, prevents fibroblast differentiation to myofibroblasts and significantly reduces tumor progression when combined with low-dose chemotherapy (12).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between cancerous cells and the adjacent microenvironment transforms the stroma into an abnormal phenotype, altering normal function (1,2). The altered stromal microenvironment affects tissue architecture, cellular morphology, and extracellular matrix (ECM)-cell interactions that directly contribute to formation of the neoplasia (1). Solid tumors, in particular breast tumors, are characterized by pathologic desmoplasia, resulting in increased fibrosis and ECM deposition (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…The altered stromal microenvironment affects tissue architecture, cellular morphology, and extracellular matrix (ECM)-cell interactions that directly contribute to formation of the neoplasia (1). Solid tumors, in particular breast tumors, are characterized by pathologic desmoplasia, resulting in increased fibrosis and ECM deposition (1,2). About 80% of reactive stroma associated with breast carcinoma is composed of activated myofibroblasts (3), which secrete ECM proteins, resulting in desmoplasia and breast tumor progression (4).…”
Section: Introductionmentioning
confidence: 99%
“…When CD49f hi Trop2 hi cells were selected from the basal fraction, transfected with Akt/Erg vectors and transplanted to induce initiation of prostatic intraepithelial neoplasia [57]; these basal cells derived from primary benign human prostate tissue initiated PC in immunodeficient mice [24]. It was also reported that Lin [59].…”
Section: Basal Cell-of-originmentioning
confidence: 99%
“…Combining docetaxel with the EGFR-targeting agent cetuximab and the antiangiogenic agent sunitinib (SUTENT) inhibits tumor growth approximately 50% at the end of the 3 rd week dosing schedule [126]. Targeting the fibroblast-to-myofibroblast transition with halofuginone (inhibitor of collagen type I) may also synergize with low doses of chemotherapy in achieving a significant antitumor effect, avoiding the need of high-dose chemotherapy and its toxicity without impairing treatment efficacy [57]. These results all support the idea that targeting PCSCs, their further differentiated progenies, and microenvironment could be more effective to counteract PC transition to invasive and metastatic stages.…”
Section: New Therapeutic Approaches In Targeting Pcscsmentioning
confidence: 99%